2018
DOI: 10.3390/molecules23092209
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Phytochemical Profiles and Antioxidant Enzyme Activity Analyses of the Southern Highbush Blueberry (Vaccinium corymbosum) at Different Developmental Stages

Abstract: In this study, the fruit quality, anthocyanin content and antioxidant enzyme activities of skin and pulp of southern blueberries (Vaccinium corymbosum) from China y at five developmental stages (green, pink, red, purple and blue) were investigated and anthocyanins were characterized and quantified by HPLC during the considered developmental stages. The results indicatated that the contents of phenolic, flavonoids and anthocyanin as well as antioxidant enzyme activities varied depending on the developmental sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 44 publications
3
31
2
2
Order By: Relevance
“…Flavonoids are a big class of polyphenolic plant secondary metabolites, including flavonols, flavones, isoflavones, anthocyanins and so on [1]. Most of the flavonoids are effective natural antioxidants [2]. In human beings, flavonoids play important roles in maintaining normal vascular permeability and protecting against diseases such as hyperglycemia, cancer, and diabetes [3].…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are a big class of polyphenolic plant secondary metabolites, including flavonols, flavones, isoflavones, anthocyanins and so on [1]. Most of the flavonoids are effective natural antioxidants [2]. In human beings, flavonoids play important roles in maintaining normal vascular permeability and protecting against diseases such as hyperglycemia, cancer, and diabetes [3].…”
Section: Introductionmentioning
confidence: 99%
“…The SOD activity showed a positive correlation with the POD activity; both these enzyme activities showed a negative correlation with the PPO activity. Superoxide dismutase is an important antioxidant enzyme that eliminates free oxygen radicals in cells, and POD plays an important role in enhancing antioxidant capacity, which promotes the oxidation of phenolics [23]. Barley grass showed relatively high SOD and POD activities in the jointing stage.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the three developmental stage groups were clearly separated by the two principal component axes, PC1 and PC2, which suggested that the compounds in barley grasses at three developmental stages could be clearly distinguished. The changes in the antioxidant enzyme activities among the different developmental stages are attributable to the transformation of chemical substances and the interaction of antioxidant enzymes [23]. The metabolism and antioxidant activity have been determined by phytochemical profiles and the enzyme activity through complex interactions at the different developmental stages of barley grasses, rather than simply being caused by the change of certain material [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, Castrejón et al found that polyphenolic compounds' concentration and antioxidant activity in highbush blueberry fruits decreased from unripe green to ripe blue stages of fruit maturity [67]. Total flavonoids and vitamin C levels in blueberry fruits were also decreased as the fruits grow [68]. Those antioxidants in green fruits were highest and blue fruits were lowest.…”
Section: Degree Of Ripenessmentioning
confidence: 94%